2012
DOI: 10.3390/molecules18010114
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Constituents of Three Allium Species from Romania

Abstract: The aim of this work was to study the chemical composition of Allium obliquum L., A. senescens L. subsp. montanum (Fries) Holub, and A. schoenoprasum L. subsp. schoenoprasum. Sulphur-containing compounds analysis was performed by an LC-MS method, the identification and quantification of polyphenolic compounds through a HPLC-UV-MS method, and the presence of five sterols was simultaneously assessed by HPLC-MS-MS. Alliin was identified only in A. obliquum and A. senescens subsp. montanum extracts, whilst allicin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
100
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(103 citation statements)
references
References 57 publications
2
100
0
1
Order By: Relevance
“…Besides, it was also concluded that medicinal plants can be involved in preventing or hindering the progression of many diseases. The herbal drugs/formulations apart from being considered as free from serious adverse effects are obtained from natural world and are easily accessible [33][34][35] . Despite the plethora of drugs developed by pharmaceutical industry, herbal remedies have proved to be effective alternative or complementary treatments for different ailments [36] .…”
Section: Resultsmentioning
confidence: 99%
“…Besides, it was also concluded that medicinal plants can be involved in preventing or hindering the progression of many diseases. The herbal drugs/formulations apart from being considered as free from serious adverse effects are obtained from natural world and are easily accessible [33][34][35] . Despite the plethora of drugs developed by pharmaceutical industry, herbal remedies have proved to be effective alternative or complementary treatments for different ailments [36] .…”
Section: Resultsmentioning
confidence: 99%
“…The method used was a previously published HPLC method with minor changes (Compaore et al, 2012;Mocan et al, 2014;Vlase et al, 2013). The method is suitable for qualitative (18 compounds) and quantitative (14 compounds) analyses.…”
Section: Plant Materialsmentioning
confidence: 99%
“…The method is suitable for qualitative (18 compounds) and quantitative (14 compounds) analyses. In this study, 18 standards of the polyphenolic compounds were used, namely caftaric acid, gentisic acid, caffeic acid, chlorogenic acid, paracoumaric acid, ferulic acid, sinapic acid, hyperoside, isoquercitrin, rutoside, myricetol, fisetin, quercitrin, quercetol, patuletine, luteolin, kaempferol, and apigenin (Mocan et al, 2014;Vlase et al, 2013).…”
Section: Plant Materialsmentioning
confidence: 99%
See 2 more Smart Citations